Experiments for Democracy during the Culture Revolution in China - Jiahong, He (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2019)
The democratic system based on political consultation and the people’s congress in PRC belongs to the category of indirect democracy, in which the key is to guarantee those in power represent the public’s interests. The Cultural Revolution was an attempt for this purpose and gave Chinese people a chance to experience some practices of mass democracy, including the democratic supervision in the form of mass criticism, the democratic governance in the form of rebellion and usurping, and the democratic participation in the form of Trinity. However, the Culture Revolution became a national disaster. With lessons learned, the Chinese leadership recognized the importance of the rule of law.